A Critical Framework to Develop Human-Centric Positive Energy Districts: Towards Justice, Inclusion, and Well-Being - Nguyen, Minh-Thu; Batel, Susana (Frontiers in Sustainable Cities, 2021)
Positive Energy Districts (PEDs) are a new energy initiative from European member states. They are, simply put, local districts which create more energy than they consume. PEDs are expected to adopt a more human-centric perspective in order to create more liveable and sustainable urban neighbourhoods. However, as previous research on energy transitions has demonstrated, the mainstream approach and technocratic tradition of research and policy vis-à-vis energy transition could result in the perpetuation of social inequalities, energy injustices, and the passive participation of citizens also within PEDs. Hence, it is crucial in these early days of PEDs to discuss what a human-centric approach should entail and how it should be enacted. Based on a narrative literature review of critical social sciences’ energy research (and specifically from social and environmental psychology), this paper will propose a critical framework containing five key dimensions which are relevant for creating more just and inclusive PEDs. These are: uncertainty, risk perception and trust; distributive justice; recognition justice and people-place relations; procedural justice; and, routines, capabilities and lived experiences. To that end, it will also discuss the different implications of mainstream and critical approaches in energy research and social sciences in relation to the deployment of human-centric PEDs. The review concludes that in order to successfully deploy human-centric PEDs, a critical approach is needed and presents some concrete recommendations for future research and policy in order to adopt such an approach. These include: considering justice, inclusion and the well-being of affected socio-ecological systems in the whole-life cycle of PEDs; better integration of indigenous capabilities; and, an ethos of de-growth and circularity in their deployment.